Phytochemical Studies and Bioactivity Tests of Murraya Paniculata Jack, Aegle Marmelos Correa and Zingiber Amaricans Blume - Riyanto, Sugeng (2003)
South East Asian countries are very rich in biodiversity with thousands of the plants species of which only a small proportion of the species have been investigated in detail. This research was carried out to investigate the chemical constituents and bioactivities of three well known medicinal plants Murraya paniculata Jack, Aegle marmelos Correa (Rutaceae) and Zingiber amaricans Blume (Zingiberaceae). Leaves and stem bark of M paniculata; leaves, bark and root of A. marmelos and rhizomes of Z. amaricans were separately extracted with various solvents. The extracts and isolated pure compounds were examined for their bioactivity against microbes and cancer cell line. Cytotoxic assay was performed against CEM-SS (human T-Iymphoblastic leukaemia) cell line with MIT reagent, while antimicrobial tests were conducted by diffusion method against a list of the pathogenic bacteria and fungi. The structures of the isolated compounds were elucidated by using spectroscopic methods.